Voltage Stability of Weak Sending-end System with Large-Scale Grid-connected Photovoltaic Power Plants - Feng XIAO; Minxiao HAN; Xiaojun TANG; Xin ZHANG (Zhongguo dianli)
With the rapid development of new energy power, the HVDC sending-end system in the northwest of China gradually shows the characteristics of high penetration of new energy, weak AC grid and small rotational inertia, and the voltage stability problems of the weak sending-end system caused by them cannot be ignored. Firstly, based on the static voltage sensitivity of the converter bus with large-scale grid-connected photovoltaic power plants at the sending end, the factors affecting the voltage stability of the converter bus are derived. Furthermore, a calculation process for photovoltaic grid-connected critical capacity is designed to provide a basis for site and capacity selection of PV plants. A sending-end comprehensive short circuit ratio (SCSCR) index is proposed to describe the support strength of AC system at the weak sending-end with large-scale grid-connected photovoltaic power plants. The comparison of SCSCR, SCR and ESCR shows that SCSCR is more relevant to the static voltage stability of the weak sending-end system. The SCSCR index can simplify the analytic process of voltage stability of weak sending-end system, and guide the power source organization and topology design of outbound delivery system with high penetration of new energy.